Individual and organizational barriers faced by physiotherapists in implementing evidence based practice- an analytical study - Sabiha Arshad; Muhammad Waqas Sharif, Iqra Waseem, Wajeeha Mahmood; Hafiza Saira Ilyas (Journal of the Pakistan Medical Association, 2022)
Objective: The primary objective of the study was to determine the present barriers in EBP implementation and secondary objective was to find out the routine practices other than evidence-based practice. Methods: It was an analytical cross-sectional study with a sample size of 235 participants. Non-probability convenience sampling technique was used. The data was collected after ethical approval on 01 January 2021, using Barrier Scale by Dr. Funk with written permission via email. The data was encoded and analyzed by SPSS version 16. For descriptive data Mean, Standard Deviation, Frequencies, Percentages, and tables were used to present the results and the Chi-Square test was used to show the association. Results: In this study Male 104 (44.3%) and Females were 131(55.7%) with a mean age of 31.5+9.5 years. 64.3% of Physiotherapists were having 2-5 years and 28.1% had 5-7 years of working experience. This study shows that “Insufficient time on the job to implement new ideas” is 1st barrier at the organizational level and second place, according to Mean value is “time to read research” at the individual level. Conclusion: This study shows that PTs faced barriers at both organizational and individual levels. The top barriers faced at the organizational level were inadequate facilities, not authorized to change the patient care procedure, and at the Individual level were research unawareness, limited time and not beneficial effects of variation in practice, and uncertainty of results. Keywords: Evidence Based Practice, Individual Barriers, Organizational Barriers, Physiotherapists.